Fishbone ingestion is a non-negligible cause of intestinal perforation - Zuo, Wenwei; Bai, Jiexin; Wei, Jing; Long, Chuan (Frontiers in Medicine, 2025)
Foreign body ingestion (FBI) is considered a widespread global health concern, with fishbone ingestion (FI) occurring frequently. However, fishbone-induced intestinal perforation (FIIP) remains rare and is frequently overlooked in the initial differential diagnosis. A case involving a 39-year-old patient presenting with acute abdominal pain was diagnosed as FIIP. Initial laparoscopic surgery was followed by a laparotomy for fishbone removal, resulting in a favorable patient recovery. The existing literature on FIIP is reviewed in this article. Reported cases underscore the necessity of prompt identification of the perforation’s cause and the critical role of thorough medical history-taking. Computed tomography (CT) and ultrasonography are considered essential diagnostic tools in confirming the condition. While ultrasonography serves as a rapid, non-invasive preliminary examination, CT is regarded as more accurate and comprehensive. In regions with high fish consumption, FIIP should be considered in adult patients, especially the elderly. Retained fishbones may result in serious complications and should be removed whenever feasible. Clinical education is considered vital in minimizing delays in diagnosis and treatment. The least invasive treatment strategy should be selected according to the patient’s clinical status.